2013
DOI: 10.4236/abb.2013.41005
|View full text |Cite
|
Sign up to set email alerts
|

Chilean crude extract of <i>Ruta graveolens</i> generates vasodilatation in rat aorta at subtoxic cellular concentrations

Abstract: In Chile elevated percentage of population have cardiovascular diseases, 70% of this populations is a hypertensive peoples. The Ruta graveolens (Ruta) is a medicinal plant used in different parts of the world with different therapeutics properties like dermatologic as far as anti-helmintic properties. We analyzed the vascular action measuring the tension to identify vasodilator effect of Ruta extract in normtense rat's aorta incubated and measured in isolated organ bath, and evaluating the toxicity effect in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…2 and 3 , respectively). Additionally, our previous report demonstrated the presence of cytotoxic effects with high concentrations only of the R. graveolens extract (above 400 μg/mL) using an endothelial cellular model [ 27 ]. Similarly, previous studies have demonstrated myorelaxant effects of plants from the Rutaceae family [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3 , respectively). Additionally, our previous report demonstrated the presence of cytotoxic effects with high concentrations only of the R. graveolens extract (above 400 μg/mL) using an endothelial cellular model [ 27 ]. Similarly, previous studies have demonstrated myorelaxant effects of plants from the Rutaceae family [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 3 mm length ring of these aorta was suspended between two parallel stainless-steel hooks, in an organ batch contained 5 ml of Krebs solution (NaCl 118 mM, KCl 407 mM, MgSO4 1.1 mM, KH2PO4 1.2 mM, CaCl2 1.5 mM, NaHCO3 25 nm and glucose 10 mM) maintained at a temperature of 37 °C, and bubbled with a carbogène (95% O2 and 5% CO2). The organ was subjected to a basic tension of 2 g. The contraction force of the isolated aorta was connected and measured with a Statham Gould® isometric transducer and recorded with physiography (Signal Monitor®) [14].…”
Section: Study Of the Activity Of Lycopodium Cernuum Extract On Isola...mentioning
confidence: 99%